2022
DOI: 10.1111/codi.16047
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta‐analysis of anal motor and rectal sensory dysfunction in male and female patients undergoing anorectal manometry for symptoms of faecal incontinence

Abstract: Aim: Manometry is the best established technique to assess anorectal function in faecal incontinence. By systematic review, pooled prevalences of anal hypotonia/hypocontractility and rectal hypersensitivity/hyposensitivity in male and female patients were determined in controlled studies using anorectal manometry.Methods: Searches of MEDLINE and Embase were completed. Screening, data extraction and bias assessment were performed by two reviewers. Meta-analysis was performed based on a random effects model with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 58 publications
(246 reference statements)
0
3
0
Order By: Relevance
“…53,54 A meta-analysis of 13 studies, including 2981 patients with FI and 1028 controls, indicated that the number of appropriately controlled studies evaluating anorectal manometry is small and that the risk of bias within the literature was high. 56…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…53,54 A meta-analysis of 13 studies, including 2981 patients with FI and 1028 controls, indicated that the number of appropriately controlled studies evaluating anorectal manometry is small and that the risk of bias within the literature was high. 56…”
Section: Discussionmentioning
confidence: 99%
“…53,54 A meta-analysis of 13 studies, including 2981 patients with FI and 1028 controls, indicated that the number of appropriately controlled studies evaluating anorectal manometry is small and that the risk of bias within the literature was high. 56 Although manometric profiles would ideally provide objective findings to guide optimal treatment, evidence describing the clinical value of ARP is generally lacking. 47,57,58 For example, ARP cannot reliably differentiate patients who would benefit from sacral neuromodulation therapy or colostomy creation or reversal.…”
Section: Anorectal Physiology Testing (Manometry Anorectal Sensation ...mentioning
confidence: 99%
“…[16][17][18][19][20][21] Although various studies have offered reference range values for ARM, standard consensus does not exist, and reported values vary by equipment, procedure protocol, sample size, and population studied. 10,22,23 Notably, available data on reference ranges are either primarily derived from samples of predominantly White women or those who do not report on race and ethnicity altogether, a phenomenon noted in studies of other pelvic floor disorders as well. 7,24,25 As such, interpretation of ARM values is challenging when caring for racially and ethnically diverse women.…”
Section: Why This Mattersmentioning
confidence: 99%